SISTEM MONITORING BIODIGESTER BERBASIS ARDUINO NANO - Atha Ezrafi; Yuli Fitriyani; Mariza Wijayanti (Jurnal Ilmiah Teknik, 2023)
Biogas is a renewable energy source that is now a trend among the wider community because biogas fermented from feces or organic waste is relatively easy to do by ordinary people. Biogas can be a solution to overcome rising fuel prices due to depletion of petroleum. the price of fuel that rises due to depletion of petroleum. the utilization of biogas is currently felt to be less than optimal because the control system is still manual and less effective. Biodigester is a gas collection system for methane, carbon dioxide and other mixed gases obtained from the decomposition of organic materials such as cow dung by bacteria that cause methanogens in an anaerobic biodigester. With the Smart Biodigester Control System we can see waste data and can make the system more optimal, namely with the automatic biogas control system in the biodigester. In a tank that is 40 cm high we can see the waste data in the tank and the AC motor in the tank will stop when at a height of 35 cm. Strobe is not active if the pressure value does not exceed 0.4 Bar. The DC valve is active from the pH data value exceeding 7.5. The success rate is 98%, the remaining 2% is further research.